The problem of performance typology - Mykytenko, Oksana Olehivna (Traditiones (Ljubljana), 2012)
This paper analyzes the performance process of Serbian mourning songs (tubalice) and various ethnic and folklore conditions of the functional process of this genre.
Keywords: Etnologija; ethnology; folk songs; folkloristics; Folkloristika; Ljudske pesmi; Serbia; Ethnopoetics; Srbija; žalostinke